2023
DOI: 10.1302/2046-3758.122.bjr-2022-0269.r1
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits RA-FLS cell proliferation and adhesion by regulating RAS/MAPK/FOXO/HIF-1 signal pathway in the treatment of rheumatoid arthritis

Abstract: Aims Rheumatoid arthritis (RA) is a common chronic immune disease. Berberine, as its main active ingredient, was also contained in a variety of medicinal plants such as Berberaceae, Buttercup, and Rutaceae, which are widely used in digestive system diseases in traditional Chinese medicine with anti-inflammatory and antibacterial effects. The aims of this article were to explore the therapeutic effect and mechanism of berberine on rheumatoid arthritis. Methods Cell Counting Kit-8 was used to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We detected that 10 μM CAY10603 effectively attenuated the proliferative effect of RA-FLS. TNF-α and IL-6 play pivotal roles in inflammation and bone destruction in RA because they facilitate the release of subsequent inflammatory cytokines and inflammatory responses, contributing to tissue injury, which is closely associated with RA disease progression ( Li et al, 2023b ). We measured the supernatant of RA-FLS by ELISA and found that CAY10603 downregulated the secretion of TNF-α and IL-6 inflammatory factors in RA-FLS, further suggesting that CAY10603 could delay the onset of RA, which was consistent with the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…We detected that 10 μM CAY10603 effectively attenuated the proliferative effect of RA-FLS. TNF-α and IL-6 play pivotal roles in inflammation and bone destruction in RA because they facilitate the release of subsequent inflammatory cytokines and inflammatory responses, contributing to tissue injury, which is closely associated with RA disease progression ( Li et al, 2023b ). We measured the supernatant of RA-FLS by ELISA and found that CAY10603 downregulated the secretion of TNF-α and IL-6 inflammatory factors in RA-FLS, further suggesting that CAY10603 could delay the onset of RA, which was consistent with the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a state in which there is an imbalance between oxidative and antioxidant effects in the body, and in RA, oxidative stress produces imbalanced superoxide that not only leads to chondrocyte mitochondrial dysfunction but is also capable of promoting chondrocyte apoptosis, synoviocyte death, and even subchondral ossification in joints (Jing et al, 2023; Zahan et al, 2020). FoxO is a pro‐inflammatory transcription factor and a major mediator of the pathogenesis of RA that produces inflammatory cytokines (Li et al, 2023). ROS causes tissue degeneration associated with inflammation and have a high oxidative capacity (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structure of SIL in the SDF file was obtained from the PubChem database, converted to a mol2 file via Open Babel 3.1.1 software, used Autodock MGL Tools 1.5.7 to add hydrogen bonds, detect the root, and set rotatable bonds, then saved as PDBQT format ( Li et al, 2023 ). The 3D structures of the key target proteins obtained from the PDB database were exported to the PDB file.…”
Section: Methodsmentioning
confidence: 99%